Investigation of Pressure Rise and Flame Acceleration Characteristics in a Single Channel of Wave Rotor Combustor with Spoilers. (2nd May 2019) - Li, Jianzhong; Zhang, Kaichen; Li, Wei; Yuan, Li
Abstract : A simplified single channel wave rotor combustor (WRC) experimental rig was established, in which the spoilers with different blockage ratios (BR) could be conveniently installed and disassembled. The spoilers were firstly used for WRC to improve the pressure rise. The effects of different blockage ratios on the pressure rise and flame acceleration characteristics in a single channel of the WRC were investigated. The addition of spoilers could remarkably improve the pressure rise and flame propagation speed in a single channel of the WRC. While the blockage ratio of the spoiler increases, both pressure rise and mean flame propagation speed are improved. When the spoilers with a blockage ratio of 38.91% are used, the peak pressure increases by 200% compared to that of WRC without the spoilers. When the spoilers of different blockage ratios (23.35%, 31.13%, and 38.91%) are used, it is found that the flame propagation speed is significantly improved with the increasing of the blockage ratio. Specifically, the maximum flame propagation speed reaches 55 m/s, and the maximum mean flame propagation speed is 36.95 m/s. Furthermore, combustion becomes more intense, and the flame is brighter around the spoiler.